2016
DOI: 10.1002/cphc.201600069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Drug–Drug Interactions in Hydrogel Delivery Systems: Experimental and Model Study

Abstract: To address the increasing need for improved tissue substitutes, tissue engineering seeks to create synthetic, three-dimensional scaffolds made from polymeric materials able to incorporate cells and drugs. The interpretation of transport phenomena is a key step, but comprehensive theoretical data is still missing and many issues related to these systems are still unsolved. In particular, the contribution of solute-solute interactions is not yet completely understood. Here, we investigate a promising agar-carbom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The elution time of the active molecule is also affected by surface topographies of the implants and the drug load. Biomaterials such as polymeric matrices, hydrogels and nanoporous matrices have been evaluated for this purpose [179][180][181][182][183][184][185]. Types of carrier-based drug delivery biomaterials have included dendrimers and micro-and/or nanoparticles (e.g., micro-and nanospheres, nanofibers and nanocapsules) [186].…”
Section: Drug-releasing Coatingsmentioning
confidence: 99%
“…The elution time of the active molecule is also affected by surface topographies of the implants and the drug load. Biomaterials such as polymeric matrices, hydrogels and nanoporous matrices have been evaluated for this purpose [179][180][181][182][183][184][185]. Types of carrier-based drug delivery biomaterials have included dendrimers and micro-and/or nanoparticles (e.g., micro-and nanospheres, nanofibers and nanocapsules) [186].…”
Section: Drug-releasing Coatingsmentioning
confidence: 99%
“…The elution time period of the drug molecule strictly depends upon the technical topographies integrated in implant coatings and the drug load. A range of nanomaterials including polymeric systems [76,77], hydrogel-based models [78][79][80], and nanoporous materials [81,82] have been explored for the manufacturing of drug-eluting dental implants. A novel drug delivery model should ensure drug safeguard from a hostile environment, plausible controlled release (in response to environmental stimuli like temperature or pH), and selectivity of a drug to specific organs, cells, or tissues in order to show improved pharmacodynamic parameters of the drug [83,84].…”
Section: Controlling the Drug Release From Coatingsmentioning
confidence: 99%
“…Kamath et al showed that diffusion or dissolution characteristics of drug molecules affect their release kinetics [89]. Drug release, if governed by the pure diffusion mechanism, is very quick due to the high in vivo clearance [78,79]. To attenuate the diffusional drug release of molecules, biorthogonal strategies were introduced to develop an affinity bond between the polymeric network and peptide (an affinity-based approach) that covalently links a small protein receptor and the observed tunable release rates [90].…”
Section: Controlling the Drug Release From Coatingsmentioning
confidence: 99%
“…In previous works we hypothesized that the ability of drug molecules to aggregate in dimers and trimers influences their behavior in term of drug delivery from hydrogel and it is different respect to what is happening in aqueous solutions. 37 Schematization present in Figure 2 represents the main phenomena: respect to the previous case (nonaggregative drug) the main difference is that here also the role of aggregation should be taken into account. In particular hydrogel network sequestrate drug monomers (adsorbing into the pores) that are not still available for aggregation.…”
Section: Mathematical Model For Aggregative Drugsmentioning
confidence: 99%